Variability in salt tolerance of native populations of Elymus scabrifolius (Döll) J. H. Hunz from Argentina - Zabala, Juan Marcelo (2011)
Elymus scabrifolius is a native C3 South American grass species. It is valued as forage species adapted to various environments in Argentina and is also a potential source of traits for wheat-breeding programmes. Efficient utilization of native genetic resources requires extensive collection and characterization of available material. The purpose of this study was to identify and characterize variability in salt tolerance within E. scabrifolius populations in Argentina. Specimens of E. scabrifolius were collected from a wide range of soils in Argentina, and most populations were found in saline environments with high sodium levels. Intraspecific variability in salt tolerance was estimated, and its relation to the salinity level of the populations' natural environment was assessed. A principal component analysis based on growth data distinguished lines from saline and non-saline habitats only under salt conditions. Results suggest that selecting under stressed environments is a reasonable strategy for breeding E. scabrifolius. Lines of saline origin had higher biomass under both control and saline conditions, suggesting that higher gains from selection would be obtained if germplasm from this origin was used, and tillering may be the most useful indirect selection criterion for improving salt tolerance. The association between salt tolerance, ion content and osmotic adjustment was also assessed. Salt-sensitive lines accumulated high sodium levels in leaves. However, osmotic adjustment did not correlate with the maintenance of leaf elongation rates under salinity in the genotypes included in this study.